FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN INDEKS PRESTASI KUMULATIF MAHASISWA TINGKAT I DAN II DIII KEBIDANAN STIKes MERCUBAKTIJAYA PADANG TAHUN 2018 - Dewi Susilawati; Eka Putri Prima Sari; Nur Fadjri Nilakesuma (LPPM Sikes Panca Bhakti Bandar Lampung, 2018)
Development index can be seen from human resources. The three main factors that can be determinants are education, health, and economy. These factors are related to the nutritional status of the community. Because children who get adequate food from the womb (well-nourished status) will grow and develop optimally according to their age and have a good life expectancy. In addition to nutritional factors, successful learning and academic achievement of students are also affected by anemia. There are other factors that influence learning achievement, including parents' attention, learning facilities, learning time, motivation, intelligence, interests, teacher teaching skills and so on. The purpose of this study was to determine whether there was an effect of nutritional status, anemia, psychosocial with the cumulative grade index of students grade I and II DIII Midwifery MERCUBAKTIJAYA Padang STIKES in 2018. This research was conducted on 22 February to 30 April 2018 at MERCUBAKTIJAYA STIKES Padang, with a sample of 39 students of Midwifery DIII study program with Stratified Random Sampling technique. This study was analyzed by chi-square test. The results of this study are that there is a relationship between nutritional status, anemia and student cumulative performance index where the P value is 0.008 and 0.026. There is no relationship between Psychosocial and achievement indices for students at grade I and II of DIII Midwifery Program at STIKES MERCUBAKTIJAYA Padang. The conclusion of this study are that there is a relationship between nutritional status, anemia and student cumulative performance index and no relationship between Psychosocial and achievement indices for students at grade I and II. The suggestion of this research is that students are expected to maintain their nutritional quality and require cooperation between the education and parents in maintaining supervision over the mental condition of students.